Study on Well Logging Technology for the Comprehensive Evaluation of the “Seven Properties” of Shale Oil Reservoirs—An Example of Shale Oil in the Lucaogou Formation in the Jimsar Sag, Junggar Basin - Hongyan Qi; Jing Su; Xuan Hu; Aiyu Ma; Yuqing Dong; Ang Li (Frontiers in Earth Science, 2022)
The shale oil reservoir in the Lucaogou Formation in the Jimsar Sag, Junggar Basin has a complex lithology, complex pore structure, and strong heterogeneity. Conventional logging reservoir evaluation methods have difficulty accurately evaluating the lithology, physical properties, electrical properties, oil-bearing properties, source rock characteristics, brittleness, and horizontal in-situ stress. Starting from the logging response characteristics of complex lithologies, a multilevel, multi-logging parameter combination shale oil logging evaluation is proposed, and an evaluation model of the “seven properties” of shale oil reservoirs is established. This model is used to interpret the data in the study area and achieves good results, effectively solving the “three types of quality” evaluation problems of shale oil source rock quality, reservoir quality and engineering quality. Based on the comprehensive evaluation of the seven properties of logging, it is proposed that the lithology of the Lucaogou Formation shale oil determines the physical properties, brittleness, source rock properties, rock mechanical properties, contact relationships with the reservoir and physical property controls on the oil-bearing property; the “sweet spot” of shale oil in the Lucaogou Formation is clarified, providing effective support for the development of shale oil in the Jimsar Depression.